A text-critical study on the Lukan account of the Lord’s Supper (Luke 22:17-20) : the shorter reading and its implications - Cho, Jeung Un (Stellenbosch : Stellenbosch University, 2020)
Thesis (MTh)--Stellenbosch University, 2020.